Development of novel isatin-nicotinohydrazide hybrids with potent activity against susceptible/resistant Mycobacterium tuberculosis and bronchitis causing-bacteria - Zainab M. Elsayed; Wagdy M. Eldehna; Marwa M. Abdel-Aziz; Mahmoud A. El Hassab; Eslam B. Elkaeed; Tarfah Al-Warhi; Hatem A. Abdel-Aziz; Sahar M. Abou-Seri; Eman R. Mohammed (Taylor & Francis Group, 2021)
Joining the global fight against Tuberculosis, the world's most deadly infectious disease, herein we present the design and synthesis of novel isatin-nicotinohydrazide hybrids (5a-m and 9a-c) as promising anti-tubercular and antibacterial agents. The anti-tubercular activity of the target hybrids was evaluated against drug-susceptible M. tuberculosis strain (ATCC 27294) where hybrids 5d, 5g and 5h were found to be as potent as INH with MIC = 0.24 µg/mL, also the activity was evaluated against Isoniazid/Streptomycin resistant M. tuberculosis (ATCC 35823) where compounds 5g and 5h showed excellent activity (MIC = 3.9 µg/mL). Moreover, the target hybrids were examined against six bronchitis causing-bacteria. Most derivatives exhibited excellent antibacterial activity. K. pneumonia emerged as the most sensitive strain with MIC range: 0.49-7.81 µg/mL. Furthermore, a molecular docking study has proposed DprE1 as a probable enzymatic target for herein reported isatin-nicotinohydrazide hybrids, and explored the binding interactions within the vicinity of DprE1 active site.